Diálogo ecumênico e inter-religioso para o caminho da paz - Silva Neto, Luiz Guatura da (2017)
This research seeks to address the theme “Ecumenical and Interreligious Dialogue for the Path to Peace”, seeks to discover it as the world advances in technology and continues to suffer the conflicts which is a lack of dialogue promoted. In the first chapter, we try to demonstrate a path that can promote peace and justice, so we go through Willian Carey's journey through proposals for the Week of Prayer for Christian Unity, an Edinburgh Conference in Scotland, not beginning and the various conferences held during the past tense. Subsequently, movements by the desire of Protestants in Latin America, there is no European ecumenism, reporting a vision of ecumenical dialogue within the European protest in Latin America and Brazil. In Brazil, we exposed the birth of the Pentecostal Movement from the Assembly of God, its expansions and schism in 1987, in Salvador/Bahia; An understanding of ecumenism within the Pentecostal Movement in conjunction with the General Convention of Assemblies of God in Brazil (CGADB) and a view of the amounts attached to the National Convention of Assemblies of God in Brazil (CONAMAD). We also discussed the creation of the World Council of Churches, the contribution and development of the Catholic-Lutheran dialogue to the document "Conflict in Communion" and preparations for the 500th anniversary of the Reformation. In the third chapter, we talk about ecumenism, from the decree of the Second Vatican Council Unitatis Redintegration and punctual updating from the Ecumenical Council. Already in the fourth chapter, we focused on a statement “Nostra Aetate”, which deals with interreligious dialogue, emphasizing interreligious dialogue for the construction of peace.